The Influence of Rural Development Policies of the European Union. Case Study Botosani County - Maria-Simona Cuciureanu (CES Working Papers, 2012)
The European Union created rural development policies in order to reduce disparities between member states. The policies consist in financial instruments that can be accessed for financing rural communities. The diversity of projects that can be funded denotes the complex problems that rural areas are facing on an European scale. The study has as hypothesis the evaluation of rural development in Botosani county because of Romania's accession to the European Union and its influence. Thus we can observe priority areas for accessing european funds. Qualitative and quantitative data on rural development projects are used to identify rural distribution projects and priority areas. The influence of policies and development strategies reduces intra disparities, ensuring authorities competitiveness needed to develop and implement other projects with the same goal.
Keywords: R12; R38; R58; 330; policies; strategies; rural development; European Union; disparities transport infrastructure Romania